Wearable training system with real-time biofeedback and gesture user interface. Issue 7 (October 2015) - Umek, Anton; Tomažič, Sašo; Kos, Anton
Abstract Wearable computing and sensors are becoming increasingly prevalent in our daily lives. This paper presents a wearable training system designed to facilitate the learning process of proper movement patterns in sports training. The system implements a gesture user interface and real-time biofeedback. The feedback loop consists of one or more body-attached motion sensors, a processing device and a biofeedback device that are interconnected through low-latency communication channels. Due to the diverse number of possible applications, a flexible system architecture, which includes several different system versions, is proposed. Operation of the system is driven by user gestures. To demonstrate the concept of the proposed real-time biofeedback training system, an application for golf swing training is developed. The application implements the system using smartphone motion sensors and audio biofeedback and aids golfers in correcting unwanted head movements during a golf swing. The application is driven by a gesture user interface. During the golf swing, the application provides users with real-time audio feedback that signals head movement errors. The field test results show that the developed application can be used as an efficient tool in golf swing training.